Neonatal arterial blood gases & immediate outcome following perinatal asphyxia. - Mannan, Md Abdul; Dey, Subir; Karim, SM Rezaul; Iqbal, Shahed; Yasmin, Sabina; Ferdous, Navila (Bangladesh Journal of Medical Science, 2019)
Background: Perinatal asphyxia (PNA) remains a significant cause of death and disability despite the important advances in perinatal care in the past decades. Early neonatal mortality within the first 24 hours contributes substantially to overall neonatal mortality rates. Estimates of the incidence of perinatal asphyxia vary, in resource-rich countries is about 1/1000 live births and in resource-poor countries is probably much more common, an incidence of 5–10/1000 live births and represents the second most common cause of neonatal death (24%) after preterm birth related complications (35%). About one quarter of all neonatal deaths globally are caused by PNA & an equal number of serious neurological consequences ranging from cerebral palsy & mental retardation to epilepsy. Objective: To determine how well neonatal arterial blood pH and base deficit predict immediate outcome (survival to discharge) following perinatal asphyxia. Methods: This was a prospective study conducted in the delivery room and adjacent neonatal area (NICU) of Ad-din Medical College Hospital (AMCH), over 6 months from 1st June and 30th November, 2017. Research assistants were trained to observe and record events related to labor and neonatal resuscitation. Patient information was obtained which included patient characteristics (gender, birth weight & gestational age) and APGAR scores at and beyond 5 minutes. Within one hour of delivery all admitted neonates were subjected to an arterial blood gas (ABG) analysis by GEM Premier 3000 blood gas analyzer and pH and base deficit were noted. All the neonates were classified according to GA, BW and Gender. After proper cleaning the collected data were analyzed thoroughly. Descriptive analyses were performed; differences in outcome by GA, BW, Gender, APGAR scores and ABG (pH and base deficit) status were determined using analysis of variance. Analyses were performed using the Statistical Package for Social Sciences (SPSS) version (Chi-Square test). Results: A total 50 neonates were studied in this period of which 72% survived & 28 % expired. Death was mostly observed in neonate who had very high level of base deficit (> 20mmol/L) & very low pH (pH <7.0) in 1st hour postnatal ABG. Survival rate was higher, 94.7% in >35 - <37 weeks GA group in comparison of >37 weeks (58%) of GA (p = 0.0050). The neonates with birth weight (BW ) >2000 - <2500 gm were observed 77.78% survival and 68.75% in neonates with BW >2500gm (p = 0.494). In this study most of the neonates were male (70%) & recovery rate was relatively better among baby boys (74.3%) than baby girls (66.67%) (p = 0.582). High APGAR score neonates had better rate of recovery than poor APGAR score neonates. The neonates with APGAR score 4-6 beyond 5 minutes were observed 88.33% survival & the neonates with APGAR score 0-3 beyond 5minutes were 55% survival (p= 0.028). High pH value neonates in 1st hour ABG were found higher rate of survival in comparison to low pH value neonates. It was 83.33% in pH 7.10- <7.20 neonates, 72.73% in pH 7.0- <7.10 neonates and 33.33% in pH <7.0 neonates respectively (p=0.0136). The neonates with high level of base deficit in 1st hour ABG showed lower rate of survival than low level of base deficit neonates. It was 12.5% in base deficit > 20mmol/L neonates, 33.33% in base deficit > 15 - 20mmol/L neonates & 87.18% in base deficit > 12 -15mmol/L neonates respectively (p=0.00003). Conclusion: From this study it is concluded that initial pH and base deficit of 1st hour ABG of neonates along with APGAR score at or beyond 5 minutes is a good predictor of risk & immediate outcome following perinatal asphyxia. A good percentage of neonates recover due to early diagnosis, meticulous nursing care and timely intervention. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.238-243